Interaction with potential donors' families: The professionals' community of concern—a phenomenological study - Orøy, Aud (CoAction Publishing, 2011)
The aim of this paper was to explore the health professionals' experiences and gain a deeper understanding of interaction with families of critically ill or traumatized patients with severe brain injuries. The methodological approach was qualitative and phenomenological. Data were collected through participant observation and in-depth interviews with nurses, physicians, and chaplains working in two ICUs in a Norwegian university hospital. A thematic analysis was used for analyzing data. Two main themes emerged from analysis: Patient oriented even when present and Family oriented even when absent. Each main theme is divided into two sub-themes. The themes appeared as phases in an interaction process. In the two first phases the interaction may be characterized as Alternating between being absent and present and Following up and withholding information and in the two last phases as Turning point and changing focus and Partly present when waiting for death. The findings are in the discussion illuminated by the phenomenological concept of concern. Concern is visible as care, and the distinction in care between “leaps in” and “leaps ahead” and “ready-to-hand” and “unready-to-hand” are topics in the discussion. Because of the complexity of caring for both patient and family, the situation demands efforts to relieve nurses in particular, during the most demanding phases of the process.